Survival of Listeria monocytogenes on irradiated chicken carcasses during cold storage - Radziah Ariffin (Unit Tenaga Nuklear, Bangi, Selangor Darul Ehsan (Malaysia)) (Impaque Publishing, 2013)
The effect of gamma irradiation on the survival of Listeria monocytogenes on poultry carcasses during cold storage was studied. Freshly processed poultry carcasses were inoculated with Listeria monocytogenes at 10 to the power of 2, 10 to the power of 4 and 10 to the power of 6 Cfu/10cm square root. The carcasses were irradiated at 2.5 kGy and then were stored at 5 degrees centigrade, 1 degrees centigrade for 3 days and subsequently at 10 degrees centigrade, for 21 and 7 days respectively. The number of Listeria monocytogenes on chicken carcasses as well as the number of Listeria - positive carcasses were reduced by 2.5 kGy of gamma irradiation, however, this dose level did not guarantee Listeria - negative products. Immediately after irradiation, about 10 percent of the carcasses inoculated with 10 to the power of 2 Cfu/10cm to the power of 2, which is more consistent with natural contamination, was positive for Listeria monocytogenes. Prolonged storage enabled the organism to recover and subsequently grow, especially when the carcasses were stored at temperatures more conducive to Listeria growth, i.e. 1 degree centigrade